Simultaneous Photoactivation of cGAS‐STING Pathway and Pyroptosis by Platinum(II) Triphenylamine Complexes for Cancer Immunotherapy - Ling, Yu‐Yi; Xia, Xiao‐Yu; Hao, Liang; Wang, Wen‐Jin; Zhang, Hang; Liu, Liu‐Yi; Liu, Wenting; Li, Zhi‐Yuan; Tan, Cai‐Ping; Mao, Zong‐Wan (Angewandte Chemie International Edition, 2022)
Activation of the cyclic GMP‐AMP synthase‐stimulator of the interferon gene (cGAS‐STING) pathway is a potent anticancer immunotherapeutic strategy, and the induction of pyroptosis is a feasible way to stimulate the anticancer immune responses. Herein, two PtII complexes (Pt1 and Pt2) were designed as photoactivators of the cGAS‐STING pathway. In response to light irradiation, Pt1 and Pt2 could damage mitochondrial/nuclear DNA and the nuclear envelope to activate the cGAS‐STING pathway, and concurrently induce pyroptosis in cancer cells, which evoked an intense anticancer immune response in vitro and in vivo. Overall, we present the first photoactivator of the cGAS‐STING pathway, which may provide an innovative design strategy for anticancer immunotherapy. The first small molecule that can activate cGAS‐STING in a photocontrollable way is reported. Upon irradiation, Pt1 and Pt2 can damage mitochondrial DNA, the nuclear envelope and nuclear DNA sequentially, which effectively releases DNA into cytoplasm to activate the cGAS‐STING pathway both in vitro and in vivo.